2021
DOI: 10.31849/utamax.v3i1.6166
|View full text |Cite
|
Sign up to set email alerts
|

Post-Pandemic of Covid-19 and the Need for Transforming Education 5.0 in Afghanistan Higher Education

Abstract: The study is aimed to lead the global educational transformation in Afghanistan to prepare higher education institutions for the post-pandemic of Covid-19. Today, the purpose of education has changed. Everything is just a click away; One can google the right answer. Therefore, there is an urgent need for redefining the national educational objectives and set new goals that are aligned with the new norms. The 21st-century learners are involved in an education that cooperates with their head, hearth, and hands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 11 publications
0
23
0
9
Order By: Relevance
“…After scrutinizing the textbook, it is revealed that the textbook widely relies on the GMT (Grammar-Translation Method). According to Rahim (2021), in GMT, language is taught through reading and translation skills and the focus is on memorization. In the textbook, a considerable focus is given to the reading section, and after the reading, there are some activities such as fill in the blanks and comprehension questions from the text.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After scrutinizing the textbook, it is revealed that the textbook widely relies on the GMT (Grammar-Translation Method). According to Rahim (2021), in GMT, language is taught through reading and translation skills and the focus is on memorization. In the textbook, a considerable focus is given to the reading section, and after the reading, there are some activities such as fill in the blanks and comprehension questions from the text.…”
Section: Methodsmentioning
confidence: 99%
“…In the textbook, a considerable focus is given to the reading section, and after the reading, there are some activities such as fill in the blanks and comprehension questions from the text. Besides, in the GTM, colossal attention is given to grammar, but little attention is given to the use of language for communication where teaching and learning are not aligned with Education 5.0 (Rahim, 2021). In the textbook, as mentioned earlier, considerable attention is given to grammar.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tiffany Barnes, for example, analyzed and concluded that the application of AI technology can be an effective tool to promote learning and teaching efficiency through the application of AI in computer teaching. Rahim et al explain what benefits the Internet can bring to teaching and learning [11]. It is mentioned that Internet applications not only help to improve the richness of teaching content but also help students to break through the time and space constraints and make better use of fragmented time for learning.…”
Section: Current Status Of Researchmentioning
confidence: 99%